Results from the PROmoting Early Childhood Outside cluster randomized trial evaluating an outdoor play intervention in early childhood education centres - Rachel Ramsden; Dawn Mount; Yingyi Lin; Emily Fox; Susan Herrington; Janet Loebach; Adina Cox; Anita Bundy; Amber Fyfe-Johnson; Ellen Beate Hansen Sandseter; Michelle Stone; Mark S. Tremblay; et al. (Scientific Reports)
Abstract Participation in outdoor play is beneficial for the health, well-being, and development of children. Early childhood education centers (ECECs) can provide equitable access to outdoor play. The PROmoting Early Childhood Outside (PRO-ECO) study is a pilot randomized trial that evaluates the PRO-ECO intervention on children’s outdoor play participation. The PRO-ECO intervention included four components: ECEC outdoor play policy; educator training; ECEC outdoor space modification; and parent engagement. This study included eight ECECs delivering licensed care to children (n = 217) aged 2.5 to 6 years in Greater Vancouver, British Columbia, Canada. Using a wait-list control cluster randomized trial design, ECECs were randomly allocated to either the intervention arm (n = 4) or the wait-list control arm (n = 4). Change in the proportion and diversity of observed outdoor play behaviour during scheduled outdoor time was measured. Outcome data were collected at baseline, 6-month follow-up, and 12-month follow-up. The intervention effect on children’s outdoor play participation was examined using logistic regression mixed effect models. Controlling for gender, weather and temperature, there were no changes in children’s outdoor play participation following implementation of the PRO-ECO intervention in the between-group analysis. Within-group comparisons also revealed no change in play participation following the PRO-ECO intervention, however, the intervention group showed a positive effect (OR = 1.28, 95% CI = 0.97, 1.70) in play participation 6 months after implementation of the intervention. The findings indicate that further analyses on child- and ECEC-level outcomes collected as part of the PRO-ECO study, including the diversity of children’s play, is required to effectively assess the impact of this intervention.